Life-cycle assessment method for key parts of an electric locomotive body - ZENG Yanjun; JIN Xihong; ZHU Tao; LIU Hongye; ZHANG Huahai (机车电传动)
In respect of the fatigue crack failure of the electric locomotive body under the cyclic excitation, the dynamic strain test was carried out on the key parts, and the fatigue life of the locomotive body was researched based on standard loads. Firstly, the body of an electric locomotive was taken as the research object, the dynamic strain test of the key parts was carried out, and the test data were filtered by low-pass filter. Secondly, the rainflow counting was carried out on the filtering results, and the parameters of the welding material at the measuring point were determined based on the IIW (International Institute of Welding) standard. The fatigue crack initiation life of the key parts was calculated according to the Palmgren-Miner linear cumulative damage theory. Then, the body bolsters and the local structure of the underframe of the vertical damper holder were taken as examples, the sub-model of crack propagation simulation of key parts was established, and the load conditions of the sub-model were determined based on the EN 12663 standard. Finally, the initial crack was inserted at the dynamic strain measuring point of the vertical damper, and the fatigue crack propagation life was calculated based on the fracture mechanics, thereby obtaining the fatigue life data of the vertical damper holder of the body. The results show that the fatigue crack initiation life of the vertical damper holder is 6.86×107 km. Under the load conditions required by the EN 12663 standard, the electric locomotive body with an initial semi-elliptical surface crack of 2 mm in half length and 0.8 mm in depth can bear at least 4.18×107 load cycles before it completely loses its bearing capacity. The research results provide reliable test and simulation basis for the necessary improvement of the body structure, as well as a strong guidance and reference value for the evaluating the safety and reliability of the body in locomotive operation.